Cowboy come home - Bloom, Carly; Richardson, Sara (Romance fiction writer) (Bloom, Carly. Once upon a time in Texas novel., 2020)
Some cowboys aren't cut out to be Prince Charming---and Claire Kowalski knows that better than anyone. She gave her heart to Ford Jarvis two years ago, yet that didn't keep him from disappearing into the sunset. Now that he's back in Big Verde, Texas, she's determined not to make the same mistake twice. But the ruggedly sexy cowboy still knows how to push all her buttons, and avoiding him is nearly impossible when she needs his help. Ford didn't plan on returning home---ever---but when he hears that the Kowalski ranch is in trouble, he hightails it back to town. He's not eager to be reminded of the life he can never have, but his time in Big Verde is only temporary. He'll stay long enough to get the ranch up and running, then hit the road again. But when Ford finds out the new foreman he's training is Claire, still as stubborn and beautiful as ever, this cowboy is going to have to decide what matters most---repeating the mistakes of the past or fighting for a future with the only woman he's ever loved..